(untitled) (Journal of the College of Basic Education, 2022)
The gas radon is one of the main sources of natural radiation which has three types of isotopes is Rn-222 , Rn-220 and Rn – 219 and isotope is the first among the most important isotopes of the fact that a relatively long half – life (3.82 day).The igneous rocks ofthe most important source of radon in nature in addition to soil erosion resulting from these rocks and construction materials such as cement and rocks which are the basic components. The water used for drinking or for cleanliness or ground waterUsed in this research cumulative indirect way to measure the concentration of radon, which relies on the use of reagents impact of nuclear- based soild- state where the advantage of these reagents as you record and store the effects of charged particles and a long period of time.Were distributed impact nuclear organic reagent (CR-39) in the middle of several places of the residential house in the basement and the upper and after a period of time atemrt every two months during the summer and winter collected from new and conducted a chemical process skimming. After conducting measurement found that the top floor of the house contains high concentrations of radon gas, especially in the winter, and these concentrations ranged between (129.2 to 141.3 Bq-m-3), however, this focus is within the permissible limits which is estimated (200 Bq-m-3) according to the recommendations of the international commission on radiological protection.